The Chicago Blackhawks : greatest sports business turnaround ever? - Shein, James B., 1942-; Kannry, Scott ([London] : SAGE, 2016)
This case explores the turnaround and corporate renewal of the Chicago Blackhawks professional hockey team, which transformed from one of the worst-run organizations in all of professional sports in 2007 to one that won the Stanley Cup in 2010.
Originally Published in: Shein, J., & Kannry, S. (2012). The Chicago Blackhawks: Greatest Sports Business Turnaround Ever. 5-112-007. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Chicago Blackhawks (Hockey team); Sports administration -- Case studies; Corporate turnarounds -- Case studies